EFFECTIVENESS OF CONDUCTING COVERT INVESTIGATIVE (SEARCH) ACTIVITIES AND THEIR IMPACT ON ACHIEVING THE OBJECTIVES OF CRIMINAL PROCEEDINGS - Soroka, Mariia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: this article examines the necessity of researching the effectiveness of covert investigative (search) activities in criminal proceedings, determining their impact on achieving criminal procedure objectives, and evaluating their compliance with international human rights standards. Special attention is given to analyzing the judicial control mechanism for covert investigative activities, identifying problematic aspects of national legislation and law enforcement practice, including the formalized nature of decision-making procedures by investigating judges and limited access of the defense to covert investigative materials. The article also examines European Court of Human Rights jurisprudence regarding the balance between state interests in crime investigation and guaranteeing individual rights, and develops proposals for improving the mechanism of conducting covert investigative activities to ensure their effectiveness and legality. Research methods: general dialectical method of scientific inquiry, comparative legal analysis, statistical methods, scientific cognition, and hermeneutical method of legal norm interpretation. Results: an analysis of the effectiveness of covert investigative activities in Ukraine’s criminal procedure was conducted. The research examined the increasing dynamics of authorized covert investigative activities, particularly under martial law conditions, and identified several problems related to the formalistic approach to judicial oversight of these activities. The study outlines risks of unjustified use of covert investigative activities that may lead to constitutional rights violations, decreased evidentiary standards, and potential abuses by law enforcement agencies. Discussion: the study establishes that the absence of statistical data regarding the effectiveness of covert investigative activities and limited defense access to case materials complicates objective assessment of their appropriateness. The article proposes improvements to the judicial control mechanism for covert investigative activities to ensure balance between state interests in combating crime and human rights guarantees.